Oral Mucositis with Abiraterone Acetate: A Therapeutic Dilemma - Valame, Shaunak; Chandra, G; Panda, Dipanjan; Sharma, Atul (Indian Journal of Medical and Paediatric Oncology, 2020)
Mucositis is a common complication of cancer treatment. Mucositis has varied etiology. Here, we describe a case of 71-year-old male with metastatic castrate-resistant carcinoma prostate who developed mucositis with the use of targeted therapy, and this particular scenario led to the therapeutic dilemma.
Keywords: Abiraterone acetate; metastatic castration-resistant prostate cancer; mucositis